Evaluation of introduced cowpea breeding lines for Aphid (Aphis Craccivora) and bruchid (Callosobruchus Rhodensiansus) resistance in South Africa - Letsoalo, Isaac Motsoeng (University of Limpopo, 2015)
Refer to document
Thesis (M.Sc. (Agricultural Agronomy)) --University of Limpopo, 2015
Keywords: Aphid infestation; Cowpea aphid; Bruchid infestation; Cowpea bruchid; Breeding lines; Cowpea; Breeding